Differential effects of the recombinant type 1 ribosome-inactivating protein, OsRIP1, on growth of PSB-D and BY-2 cells - Chen, Simin; Gistelinck, Koen; Verbeke, Isabel; Van Damme, Els J. M. (Frontiers in Plant Science, 2022)
Plant suspension cells were treated with recombinant OsRIP1, a type 1 ribosome-inactivating protein (RIP) from rice (Oryza sativa L.). OsRIP1 triggered cell death in tobacco BY-2 cells but not in Arabidopsis PSB-D cells. Phenotypic changes in BY-2 cells exposed to OsRIP1, included loss of growth capacity, loss of integrity of the plasma membrane and vacuolar collapse. These effects were also accompanied by RNA degradation and DNA fragmentation. Targeting of exogenous OsRIP1 to plant vacuoles and OsRIP1-induced accumulation of transcripts for vacuolar processing enzymes (VPEs) indicated that OsRIP1 provoked plant cell death in tobacco BY-2 cells through the activation of VPEs and subsequent vacuolar disruption, which was probably independent of its N-glycosylase activity on cytosolic ribosomes. Necrosis with limited production of H2O2 was observed after infiltration of high concentrations of OsRIP1 in epidermal cells of Nicotiana tabacum cv. Samsun NN plants. Our study provides the first evidence that OsRIP1 exerts differential effects on the growth of PSB-D and BY-2 cells. The vacuole-dependent cell death pathway is associated with the lethal effect of the exogenously applied OsRIP1 on BY-2 cells.